Property Product Recommendation System as a Marketing Strategy at PT Java Abadi Sejahtera - Siti Munawaroh; Achmad Choiron; Ratna Nur Tiara Shanty (CV.RIZANIA MEDIA PRATAMA, 2025)
This study addresses the challenges faced by PT. Java Abadi Sejahtera in matching customer needs with available property products and the frequent data loss caused by manual recording processes. A web-based recommendation system was developed using the Profile Matching method, where criteria such as property type, location, size, price, payment method, and facilities are weighted according to their importance and processed using GAP calculations to determine the suitability between customer requirements and product data. Black box and white box testing results indicate that the system functions correctly and is able to process product data, customer member data, and follow-up data accurately. The system generates ranked product recommendations based on suitability calculations. The findings demonstrate that the recommendation system effectively supports marketing decision-making, improves the efficiency of the matching process, and enhances the overall quality of marketing strategies implemented by the company.